Priming and stress under high humidity and temperature on the physiological quality of Brachiaria brizantha cv. MG-5 seeds (Acta Scientiarum. Agronomy, 2016)
Palisade grass is a forage plant that is widely used in pasture cropping in the Brazilian savannah. The aim of this experiment was to evaluate palisade grass (Brachiaria brizantha cv. MG–5) seeds subjected to priming and stress at high humidity and temperature (before and after conditioning). The experimental design was completely randomized in a 2x5 factorial arrangement. Seeds were exposed to stress under high humidity and temperature (before and after conditioning) and five priming treatments [Water (Control), potassium nitrate (KNO3) at 0.2%, calcium nitrate Ca(NO3)2 at 0.2%, gibberellin (GA3) at 0.2% and glucose at 10%] with four replications. Two experiments were performed: Experiment I - seed with chemical scarification using H2SO4 and Experiment II - without scarification. The stress on the seed was applied using artificial aging at 41°C for 96 hours. Seed priming was accomplished by immersion at 25°C for 2 hours. Thereafter, the seeds were oven-dried at 35°C until they regained hygroscopic equilibrium. Seed germination and vigor were evaluated. Priming using KNO3 and Ca(NO3)2 produced seeds with high tolerance to stress under high temperature, and this process is efficient to overcome dormancy.